Exogenous Melatonin Ameliorates Pontine Histoarchitecture and Associated Oxidative Damage in Sodium Fluoride Induced Toxicity - Ajoke, Sulaimon Fatimo; Ayodeji, Okesina Akeem; Leken, Imam Abubakar; Yetunde, Usman Ruqayyah; Abiodun, Ibrahim-Abdulkareem Rukayat; Aminu, Imam; Yetunde, Adana Misturah; Monsur, Shehu; Raheem, Abioye Adesola ‘Idowu; Iyabo, Ayuba Aishat; Salihu, Ajao Moyosore (Nepal Journal of Neuroscience, 2020)
Background: Sodium fluoride (NaF) is a highly consumed food additive, that is capable of disrupting the activities of several brain areas. whether this compound affects the autonomic activities of the brain is unclear. Objective: Therefore, the study was designed to investigate the ameliorative potentials of exogenous melatonin on sodium fluoride-induced pontine toxicity in adult male Wistar rats, as melatonin has been implicated to have a high concentration in the cerebrospinal fluid of injured brains. Method: Thirty-two rats were randomly divided into 4 groups (n=8, per group). Groups I, II.III and IV received 0.2 ml of normal saline (NS), 500 ppm of sodium fluoride (NaF) via their drinking water, 10 mg/kg melatonin (MLT), and melatonin with sodium fluoride concurrently (MLT+NaF) respectively for fourteen days. At the end of these treatments, the rats were euthanized and brainstem tissues were excised for histological, histochemical, and biochemical analyses. Results: There were shreds of evidence of DNA fragmentation, vacuolation, dispersion of the Nissl bodies, and axonal disruption in the cells of the basilar pons of the sodium fluoride-treated animals; this was coupled with high concentrations of malondialdehyde and low-level concentrations of glutathione reductase. Melatonin, however, was observed to limit neuronal injury in the cells of the basilar pons in the experimental animals by reducing the extent of cells undergoing process pyknosis, chromatolysis, and demyelination. Also, melatonin was able to reduce the concentration of malondialdehyde and increase glutathione reductase activities in the pons. Conclusion: This study revealed that sodium fluoride injured the pontine histoarchitecture, and induced oxidative damage which were ameliorated by exogenous melatonin treatments.